EUTHANASIA: ETHICAL, MEDICAL, AND SOCIAL IMPLICATIONS - Ishqobilova Hulkar; Rustamova Sabina (TADQIQOTLAR, 2026)
Annotation. This article provides a comprehensive overview of euthanasia and its various forms. It examines the potential outcomes and implications of practicing euthanasia through three distinct perspectives: social, medical, and ethical. The study explores the ongoing debate between the "right to live" and the "right to die" in a modern context. Furthermore, the paper concludes with an analysis of a diagram illustrating common constraints—personal, social, and religious—that influence public perception and the legalization of euthanasia.